In vivo expression of proteases and protease inhibitor, a serpin, by periodontal pathogens at teeth and implants. (17th April 2018) - Eckert, M.; Mizgalska, D.; Sculean, A.; Potempa, J.; Stavropoulos, A.; Eick, S.
Summary: Porphyromonas gingivalis and Tannerella forsythia secrete proteases, gingipains and KLIKK‐proteases. In addition, T. forsythia produces a serpin (miropin) with broad inhibitory spectrum. The aim of this pilot study was to determine the level of expression of miropin and individual proteases in vivo in periodontal and peri‐implant health and disease conditions. Biofilm and gingival crevicular fluid (GCF)/ peri‐implant sulcular fluid (PISF) samples were taken from healthy tooth and implant sites (n = 10), gingivitis and mucositis sites (n = 12), and periodontitis and peri‐implantitis sites (n = 10). Concentration of interleukin‐8 (IL‐8), IL‐1β and IL‐10 in GCF was determined by enzyme‐linked immunosorbent assay. Loads of P. gingivalis and T. forsythia and the presence of proteases and miropin genes were assessed in biofilm by quantitative PCR, whereas gene expression was estimated by quantitative RT‐PCR. The presence of P. gingivalis and T. forsythia, as well as the level of IL‐8 and IL‐1β, were associated with disease severity in the periodontal and peri‐implant tissues. In biofilm samples harboring T. forsythia, genes encoding proteases were found to be present at 72.4% for karilysin and 100% for other KLIKK‐protease genes and miropin . At the same time, detectable mRNA expression of individual genes ranged from 20.7% to 58.6% of samples (for forsylisin and miropsin‐1, respectively). In comparison with the T. forsythia proteases, miropin and the gingipains were highly expressed. The level of expression of gingipains was associated with those of miropin and certain T. forsythia proteases around teeth but not implants. Cumulatively, KLIKK‐proteases and especially miropin, might play a role in pathogenesis of both periodontal and peri‐implant diseases.